Interdisciplinary dialogues between domain analysis and discursive communities, epistemic communities, metatheory and invisible colleges: methodological perspectives within the scope of knowledge organization - Guimaraes, Jose Augusto Chaves [UNESP]; Tognoli, Natalia Bolfarini (Pontificia Universidade Catolica Campinas, 2024)
Domain Analysis, considered a theoretical-methodological perspective of Knowledge Organization, has been the subject of analysis in Information Science literature for two decades, and its importance in providing contextual knowledge, emphasizing the social, historical, and cultural dimensions of information, has been recognized. However, despite this recognition, the dialogues that Domain Analysis can establish with other methodological frameworks in favor of an increasingly contextualized organization and representation of knowledge for society still need to be sufficiently addressed. In this paper, we aim to analyze the cultural configuration of Domain Analysis in Knowledge Organization and establish dialogues with discursive communities, epistemic communities, metatheory, and invisible colleges to enhance methodological robustness. The results show that the interdisciplinary dialogues proposed here provide more contextualized and socially committed processes, instruments, and products for organizing and representing knowledge.
Keywords: Domain analysis; Invisible colleges; Discoursive communities; Epistemic communities; Metatheory; Knowledge organization